Animal Educational Games Based on Augmented Reality - Galang Piliang; Sidik Sidik; Nu’man Musyaffa; Muhamad Ryansyah (Jurnal Mantik, 2022)
Problems in achieving teaching and learning success are often caused by the application of learning strategies that are not appropriate and seem monotonous and even boring. One of the reasons is rooted in the conventional educational paradigm which always uses classical teaching methods and lectures. Therefore, a more interactive and interesting learning support media is needed. One example is making learning support media using Augmented Reality (AR) based educational games. AR is a combination of real and virtual objects in a real environment, running interactively in real time, and there is integration in the real world. With this educational game, it can help teachers and parents as early childhood teachers to present media or learning environments that are more effective and interactive.